Glutamate Dehydrogenase from Mycoplasma laidlawii - Yarrison, Gerald (1972)
Mycoplasma laidlawii possesses a single glutamate dehydrogenase (GDH) with dual coenzyme specificity [specificity for nicotinamide adenine dinucleotide (H) and nicotinamide adenine dinucleotide phosphate (H)]. A purification procedure is reported which results in an enzyme preparation with a specific activity of 79.5 units/mg and which displays only one significant protein band after gel electrophoresis. This one band was determined, by activity staining, to have all of the GDH nucleotide specificities. The molecular weight of the enzyme is 250,000 ± 10%, and it has a subunit size of about 48,000. The enzyme exhibits measurable activity with aspartate and pyruvate but is inactive with eight other possible substrates. Purine nucleotides do not affect the activity. The K(m) for reduced nicotinamide adenine dinucleotide was 1.8 × 10(−4)m. The optimal substrate concentrations and pH optimum for each of the respective GDH activities are also reported.